Thailand's Missing Marine Fisheries Catch (1950–2014) - Derrick, Brittany; Noranarttragoon, Pavarot; Zeller, Dirk; Teh, Lydia C. L.; Pauly, Daniel (Frontiers in Marine Science, 2017)
Overexploitation of marine resources has led to declining catches in many countries worldwide, and often also leads to fishing effort being exported to waters of neighboring countries or high seas areas. Thailand is currently under pressure to curb illegal fishing and human rights violations within its distant water fleets or face a European Union import ban. Simultaneously, Thailand is attempting to reduce fishing effort within its Exclusive Economic Zone (EEZ). Crucial to these endeavors is a comprehensive knowledge of total fisheries catches over time. A reconstruction of fisheries catches within Thailand's EEZ and by Thailand's fleet in neighboring countries' EEZs was undertaken for 1950–2014 to derive a comprehensive historical time series of total catches. This includes landings and discards that were not accounted for in official, reported statistics. Reconstructed Thai catches from within Thailand's EEZ increased from approximately 400,000 t·year−1 in 1950 to a peak of 2.6 million t·year−1 in 1987, before declining to around 1.7 million t·year−1 in 2014. Catches taken by Thai vessels outside their own EEZ increased from 52,000 t·year−1 in 1965 to a peak of 7.6 million t·year−1 in 1996, before declining to around 3.7 million t·year−1 by 2014. In total, reconstructed catches were estimated to be nearly three times larger than data reported by Thailand to the Food and Agriculture Organization of the United Nations (FAO). Reconstructed Thai distant-water fleet catches were almost seven times higher than the comparable non-domestic catch deemed reported for Thailand. Thai landings from recreational fishing were conservatively estimated for the first time, and while they contributed less than 1% of current catch, they can be expected to grow in volume and importance with increasing tourism. As Thailand takes measures to reduce fishing effort within its EEZs and increases monitoring and enforcement of illegal and foreign fishing, it should take note of the present catch reconstruction as a comprehensive historical foundation that can point to needed improvements in data collection, policy development, and monitoring and enforcement.